CoFe2O4-Graphene Nanocomposites Synthesized through An Ultrasonic Method with Enhanced Performances as Anode Materials for Li-ion Batteries - Xiao, Yinglin; Li, Xiaomin; Zai, Jiantao; Wang, Kaixue; Gong, Yong; Li, Bo; Han, Qianyan; Qian, Xuefeng (Nano-Micro Letters, 2014)
CoFe2O4-graphene nanosheets (CoFe2O4-GNSs) were synthesized through an ultrasonic method, and their electrochemical performances as Li-ion battery electrode were improved by annealing processes. The nanocomposites obtained at 350 °C maintained a high specific capacity of 1,257 mAh g−1 even after 200 cycles at 0.1 A g−1. Furthermore, the obtained materials also have better rate capability, and it can be maintained to 696, 495, 308, and 254 mAh g−1 at 1, 2, 5, and 10 A g−1, respectively. The enhancements realized in the reversible capacity and cyclic stability can be attributed to the good improvement in the electrical conductivity achieved by annealing at appropriate temperature, and the electrochemical nature of CoFe2O4 and GNSs during discharge–charge processes.